A study of geogrid-reinforced ballast using laboratory pull-out tests and discrete element modelling - Chen, Cheng; McDowell, Glenn R.; Thom, N.H. (Taylor & Francis, 2013)
This paper presents an evaluation of the behaviour of geogrid-reinforced railway ballast. Experimental large box pull-out tests were conducted to examine the key parameters influencing the interaction between ballast and the geogrid. The experimental results demonstrated that the triaxial geogrid outperforms the biaxial geogrid and the geogrid aperture size is more influential than rib profile and junction profile. The discrete element method (DEM) has then been used to model the interaction between ballast and geogrid by simulating large box pull-out tests and comparing with experimental results. The DEM simulation results have been shown to provide good predictions of the pull-out resistance and reveal the distribution of contact forces in the geogrid-reinforced ballast system. Therefore, the calibrated geogrid model and the use of clumps to model ballast particles hold much promise for investigating the interaction between geogrids and ballast and therefore optimising performance.